Self-assembly monomolecular layer uniform membrane preparation method and application

By using NiOx and sponge metal oxide layer combined with a pull coating process in perovskite solar cells, the problem of interface defect passivation in large-area perovskite modules is solved, and the battery performance is significantly improved and stability.

CN119521996APending Publication Date: 2025-02-25JIUYAO OPTOELECTRONICS
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411626278.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Existing perovskite solar cells have problems with significant decreases in short-circuit current density, open-circuit voltage and filling factors in large-area modules, mainly due to the failure to effectively solve the defect passivation problem of large-area uniformity of the upper and lower interfaces of perovskite films.

Method used

The NiOx layer and the sponge-like metal oxide layer are deposited successively on the transparent conductive substrate, and combined with the pull coating process, a uniform and dense SAM molecular layer is formed to improve the wettability of the perovskite coating substrate.

Benefits of technology

The large-area and efficient preparation of dense and uniform SAM molecular layer is achieved, which significantly improves the VOC, FF and PCE performance of perovskite solar cells, and improves the photothermal stability and humidity stability of the device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_4
    Figure SMS_4
  • Figure SMS_5
    Figure SMS_5
  • Figure SMS_6
    Figure SMS_6
Patent Text Reader

Abstract

The invention discloses a preparation method of a self-assembled monomolecular layer, which comprises the following steps: firstly, sequentially depositing a NiOx layer and a spongy metal oxide layer on a transparent conductive substrate, and then immersing the transparent conductive substrate in an SAM precursor solution for pulling coating and baking to form the uniform self-assembled monomolecular layer. The self-assembled monomolecular layer has a uniform and compact monomolecular layer structure, can provide more passivation sites for the perovskite layer, has a relatively low surface contact angle, is beneficial to promoting the acquisition of a compact, uniform and void-free perovskite layer, can effectively inhibit a shunting path between FTO and perovskite, passivates defects at a bottom interface of the perovskite, and improves the performance of the perovskite. Non-radiative recombination is reduced, VOC, FF and the like are remarkably improved, and meanwhile the stability performance of a packaged device can be effectively improved. The large-area preparation technology of the compact and uniform SAM molecular layer can be achieved, the related preparation method is simple, the period is short, and a new thought can be provided for efficient preparation of the high-quality SAM molecular layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of perovskite solar cells, and specifically relates to a large-area uniform film-forming preparation method and application of a self-assembled monolayer. Background Art

[0002] In recent years, the laboratory efficiency of perovskite solar cells (PSCs) based on pin device structures has achieved significant breakthroughs. The latest certified efficiency reports exceeding >26.0% are all based on pin structure cells, in which the use of SAM molecules and buried interface defect passivation technology play a key role. At present, the highest efficiency of trans-pin perovskite modules reported in the literature is 22.74% (area 10-20cm 2 ) and 18.60% (area 100-200cm 2 ), compared with the existing highest efficiency of 26.54% in a small area (0.05cm 2 ) compared with the trans-pin type battery, the PCE is significantly lower. In addition, with the increase of the battery device area, there is a significant decrease in the short-circuit current density (Jsc), open-circuit voltage (Voc) and fill factor (FF); the main limiting factors include the large-area perovskite coating film, which needs to be further improved, and the large-area uniform defect passivation problem of the upper and lower interfaces of the perovskite film, which needs to be further solved.

[0003] Regarding the buried interface between perovskite and conductive glass, it is crucial to apply the SAM in high-efficiency small cells to large-area components without efficiency loss. SAM molecules can passivate the buried interface and change the work function of the buried interface. Under multiple effects, the charge transport and recombination of the buried interface can be modulated, thereby significantly improving the performance parameters of the device. Carbazole PACz-type small molecules rely on transparent conductive oxides TCO (common such as FTO / ITO) or NiO x The holes are extracted by forming a self-assembled monomer layer on the substrate through chemical and physical adsorption. Since the conductivity of this type of single-molecule material is very low, its hole transport performance is particularly sensitive to film thickness and coverage. Laboratory small-area batteries are usually prepared by spin coating, which can only guarantee 1cm 2 The thickness of the SAM molecular layer is controlled to 2-5nm to achieve TCO or NiO xRelatively uniform film coverage, thus achieving good device performance. Once the device area is slightly increased, the inherent center and edge shear velocity differences in the preparation of SAM films by spin coating will lead to uneven film thickness distribution of SAM on large-area substrates, resulting in a significant reduction in the efficiency of SAM-based trans modules. The industry usually uses solution coating to prepare thin films for large-area perovskite modules. SAM molecules are prone to rheology / crystallization / aggregation during large-area solution coating, especially for the most commonly used FTO conductive glass in industrialization. Its surface has 50-150nm of uneven ups and downs formed by FTO crystallization. It is difficult for the coated SAM molecules to form a large-area complete coverage of FTO. During coating, the SAM solution often fills the nano-sized peaks and valleys of FTO first, resulting in multi-layer SAM stacking and poor coverage; the uneven SAM molecular layer will seriously deteriorate the performance of large-area devices.

[0004] In response to the above problems, E. Yalcin et al. (E. Yalcin, Environmental Science 2019) used the immersion method to deposit SAM, but this often takes a lot of time and the film thickness control effect is not ideal. Ahmed Farag et al. (A. Farag, T. Feeney, Adv. Energy Mater. 2023) used vacuum deposition to prepare SAM molecular layers, but while increasing process costs, it also lost the process of SAM directional adsorption in the solution process. The decomposition of SAM under thermal vacuum conditions may affect the final deposition state of the SAM film and the application effect achieved. Further exploration and design of large-area preparation methods that are easy to obtain densely distributed, uniformly distributed SAM molecular layers with controllable thickness is a problem that urgently needs to be solved. Summary of the invention

[0005] The main purpose of the present invention is to provide a dense and uniform SAM molecular layer preparation process to solve the problems and shortcomings of the prior art, and to deposit NiO on a transparent conductive substrate in sequence. x layer and a sponge-like metal oxide layer, and then combined with the pull coating process to form a uniform and dense SAM molecular layer, and effectively improve the wettability of the subsequent perovskite coating substrate; this method can also achieve large-area and efficient preparation of dense and uniform SAM molecular layers.

[0006] Another object of the present invention is to provide an application of the SAM molecular layer in a perovskite battery device, wherein the SAM molecular layer can provide more passivation sites for the perovskite layer, and the wettability of the SAM molecular layer and the sponge metal oxide layer rich in hydroxyl groups on the surface is conducive to the subsequent acquisition of a dense, uniform, and hole-free perovskite layer, effectively inhibiting the carrier recombination pathway between FTO and perovskite, passivating the defects at the bottom interface of the perovskite, and significantly improving the VOC , FF and PCE and other performance.

[0007] To achieve the above object, the technical solution adopted by the present invention is:

[0008] A method for preparing a self-assembled monolayer comprises the following steps:

[0009] 1) Sequentially deposit NiO on a transparent conductive substrate x layer and metal oxide nanoparticle layer, and then sintered at high temperature to form a uniform NiO x layer and a sponge-like metal oxide layer with a mesoporous structure to obtain a substrate modified with a sponge-like metal oxide layer;

[0010] 2) immersing the obtained sponge-like metal oxide layer-modified substrate into a SAM precursor solution for pulling and coating; utilizing the capillary action of the sponge to absorb the SAM solution, and forming a uniform liquid film by gravity flow of the SAM solution during the pulling process;

[0011] 3) The coating product is baked to form a uniform self-assembled monolayer on the surface of the substrate.

[0012] In the above solution, the transparent conductive substrate can be made of FTO, ITO or AZO glass.

[0013] In the above scheme, the NiO x The thickness of the layer is 5-30 nm.

[0014] In the above scheme, the metal oxide nanoparticles are ZrO 2 or SiO 2 Insulating metal oxides such as quartz and niobium have rich hydroxyl groups on their surfaces; their particle size is 5-50nm.

[0015] In the above solution, the thickness of the sponge-like metal oxide layer is 20-150 nm, and the mesopore diameter is 5-50 nm.

[0016] In the above scheme, the NiO x The layer is sprayed; the specific preparation steps include: x The solution is evenly sprayed on the transparent conductive substrate and left to dry to form a dense NiO x The layer covers the FTO surface.

[0017] In the above solution, the metal oxide nanoparticle layer is formed by a scraping coating process.

[0018] Furthermore, the scraping process uses a metal oxide nanoparticle dispersion with a concentration of 1-3 wt %.

[0019] In the above scheme, the high temperature sintering step in step 1) includes: heating to 300-500° C. within 10 minutes, sintering at a constant temperature for 60-80 minutes, and then naturally cooling to room temperature.

[0020] In the above scheme, the SAM precursor solution is a solution of Me-4PACz, MeO-2PACz, MeO-4PACz or 2PACz, Br-2EOTm, MPA-Ph-CA, Br-2EPT, MTPA-BA or CbzNaph, and its concentration is 0.4-0.6 mg / ml.

[0021] Preferably, the SAM precursor solution is Me-4PACz, MeO-2PACz, MeO-4PACz, 2PACz or CbzNaph solution.

[0022] In the above scheme, during the pull-up coating process, the substrate modified with the obtained sponge-like metal oxide layer is immersed in the SAM precursor solution at a speed of 600-1000um / s. After being immersed in the solution, it stays for 3-6s and then is slowly lifted up at the same speed to complete the coating process.

[0023] In the above scheme, the baking temperature is 30-150° C. and the baking time is 1-15 minutes.

[0024] In the above scheme, the NiO x The area of ​​the modified transparent conductive substrate is 0.09 cm 2 above.

[0025] Furthermore, the area of ​​the sponge-like metal oxide modified transparent conductive substrate is 10 cm 2 above.

[0026] The self-assembled monolayer prepared according to the above scheme has a thickness of 2-5 nm and a uniform and compact monolayer structure, and its contact angle (water contact angle) can be reduced to 35.2°.

[0027] The invention also discloses a perovskite solar cell based on the self-assembled monolayer, wherein the perovskite layer is arranged on the surface of the self-assembled monolayer.

[0028] Furthermore, the perovskite solar cell comprises NiO arranged in sequence from bottom to top. x Modified transparent conductive substrate, self-assembled monolayer (hole transport layer), perovskite layer, electron transport layer and metal counter electrode.

[0029] In the above scheme, the electron transport layer is a common electron transport layer such as C60 or PCBM; the metal counter electrode is usually an electrode such as Cu, Ag, Al, Bi, Sn, Mo, Ni or Ti.

[0030] Furthermore, the area of ​​the perovskite solar cell is 0.09 cm 2 above.

[0031] Furthermore, the FTO / NiO x The area of ​​the substrate is 11 cm 2 above.

[0032] The perovskite solar cell prepared according to the above scheme has a small area (0.09 cm 2 )PSCs can achieve a PCE of 25.43%; the cell area is enlarged to 11.09cm 2 (the sum of the active area of ​​the solar cell plus the dead area, the same below) and 113.00cm 2 The module efficiencies of 22.64% and 20.11% can be achieved on the mini modules respectively; in addition, the packaged devices exhibit excellent photothermal stability and hydrothermal stability, retaining 92.8% and 94.4% of the initial PCE respectively after 1000 hours of continuous operation at 65°C in air at 1 sun equivalent and 500 hours of hydrothermal test (85°C / 85% RH).

[0033] The principles of the present invention include:

[0034] The present invention firstly x A layer of metal oxide nanoparticles (ZrO 2 or SiO 2 The SAM solution is then immersed in a SAM precursor solution for pulling and coating. During the pulling process, the capillary action of the mesoporous sponge pores and the gravity sedimentation during the pulling process are used to promote the SAM solution to be evenly filled into the sponge-like metal oxide layer structure and form strong chemical bonds with these oxides rich in hydroxyl groups on the surface (the introduced phosphate groups can react with NiO x The condensation reaction between the NiO nanoparticles and the hydroxyl groups on the surface of the metal oxide nanoparticles forms strong PO-Ni and PO-Zr bonds, etc., which can promote the formation of a uniformly distributed SAM layer; at the same time, the introduced non-conductive metal oxide nanoparticles can effectively compensate for the NiO x The pinholes punctured on the surface of / SAM are conducive to blocking the shunt path between FTO and perovskite.

[0035] In addition, after the self-assembled monolayer of the present invention is set on the transparent conductive substrate, the contact angle is significantly reduced (can be reduced to 35.2°), which can effectively wet the perovskite precursor solution and promote the growth of the perovskite layer; at the same time, it is beneficial to significantly reduce the defect density in the perovskite and promote the improvement of the stability performance of the packaged device (photothermal stability and wet-heat stability, etc.).

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] 1) The present invention uses NiO x -Mesoporous sponge (ZrO 2 or SiO 2 The buried interface layer of non-conductive oxides rich in hydroxyl groups on the surface (such as MgO2) as the adsorption carrier of SAM solution and combined with the pulling coating process can promote the acquisition of a dense and uniform SAM molecular layer and effectively reduce the contact angle of its surface;

[0038] 2) The self-assembled monolayer of the present invention can provide more passivation sites for the perovskite layer. At the same time, the improvement of wettability and substrate roughness is conducive to obtaining a dense, uniform and hole-free perovskite layer, which can effectively inhibit the shunting path between FTO and perovskite, passivate the defects at the bottom interface of the perovskite, reduce non-radiative recombination, and significantly improve V OC and FF, etc., and can effectively improve the stability of packaged devices;

[0039] 3) The present invention can realize a large-area preparation process of a dense and uniform SAM molecular layer, and the preparation method involved is relatively simple, has a short cycle, and has good repeatability. It can provide a new idea for the efficient preparation of high-quality SAM molecular layers, which is conducive to the further industrialization of perovskite solar cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is a schematic diagram of the preparation process of the self-assembled monolayer described in Example 1;

[0041] Figure 2 FTO / NiO obtained in Example 1 ab x / ZrO 2 Substrate and FTO / NiO obtained in Comparative Example 1 x SEM of substrate, NiO obtained by CD x / ZrO 2 / SAM and NiO x / SAM surface potential distribution, ef obtained NiO x / ZrO 2 / SAM and NiO x / X-ray photoelectron spectroscopy characterization results of SAM;

[0042] Figure 3NiO obtained in Example 1 ab x / ZrO 2 / SAM substrate and NiO obtained in Comparative Example 1 x / Wetting characteristics of SAM substrate surface, cd morphological defects of perovskite bottom surface obtained from different substrates, ef characterization results of perovskite cross-sectional morphology obtained from different substrates, g schematic diagram of pin PSCs structure, h current density-voltage (JV) curve, i steady-state PCE, j dark-state JV characteristics, k logarithmic function diagram of light intensity, l photoluminescence quantum yield of perovskite film;

[0043] Figure 4 Surface morphology of perovskite films obtained on different substrates;

[0044] Figure 5 AFM images of PVK films deposited on different substrates;

[0045] Figure 6 XRD patterns of perovskite films deposited on different substrates;

[0046] Figure 7 UV-Vis images of perovskite films deposited on different substrates;

[0047] Figure 8 Distribution statistics of various photovoltaic parameters for different devices;

[0048] Fig. 9 For different concentrations of ZrO 2 The obtained FTO / NiOx / ZrO 2 SEM image of substrate;

[0049] Fig.10 In the figure, a is FA prepared on Ni-Zr-S (Ni-S) substrate 0.85 Cs 0.15 PbI 2.85 Br 0.15 The morphology of the perovskite film and the point diagrams at different positions, bc is the JV curve of the perovskite device obtained at the corresponding positions of different substrates, de is the test result of the electronic uniformity of the perovskite obtained at different substrates;

[0050] Fig.11 The PL intensity test results of perovskite films obtained on different substrates;

[0051] Fig.12 Transient photovoltage results of perovskite films obtained on different substrates;

[0052] Fig.13 The transient photocurrent test results of perovskite films obtained on different substrates;

[0053] Fig.14 a is a schematic diagram of the structure of the perovskite device, b is a different substrate (11.09cm 2 ) The current-voltage (IV) curve of the pin PSCs obtained, c The summary results of the PCE and fill factor survey obtained within the existing trans mini module size range, d The PCE distribution statistics of the reference device and the target device, e 11.09cm 2 Steady-state PCE of target device, f FTO / NiO x / ZrO 2 Substrate (113cm 2 ) on the device efficiency obtained by different SAM layer preparation processes (spin coating or blade coating), gh PCE test results of continuous 1 sun equivalent operation at 65℃ in air for 1000 hours and damp heat test (85℃ / 85% RH) for 500 hours;

[0054] Fig.15 Preparation of SAM layer devices (113cm 2 ) surface point map;

[0055] Fig.16 Preparation of SAM layer devices (113cm 2 )’s TRPL test results;

[0056] Fig.17 Photoluminescence test results of devices obtained on different substrates;

[0057] Fig.18 Example 1 and Comparative Example 3 are respectively x The battery efficiency test results of the battery device obtained under the layer setting conditions;

[0058] Fig.19 Example 1 and Comparative Example 3 are respectively x Stability test results of the battery device obtained under the layer setting conditions. DETAILED DESCRIPTION

[0059] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0060] Example 1

[0061] A self-assembled monolayer, the preparation process diagram is shown in Figure 1 , the specific preparation method comprises the following steps:

[0062] 1) In the FTO / NiO with an area of ​​5×5cm xA layer of ZrO (thickness 10-25nm) is scraped on the substrate 2 Nanoparticle dispersion (concentration 2wt%, ZrO 2 The nanoparticles have a particle size of 5-50 nm) and are sintered. The specific steps are: heating to 500°C within 10 minutes, sintering at a constant temperature for 60 minutes, and then naturally cooling to room temperature to form a uniform sponge-like ZrO with a mesoporous structure on the substrate. 2 layer (with a thickness of 30-120nm and a mesopore diameter of 10-40nm) to obtain a sponge-like ZrO 2 Layer modified substrate (FTO / NiO x / ZrO 2 );

[0063] 2) The obtained FTO / NiO x / ZrO 2 Immersed in a concentration of 0.4 mg ml -1 The specific steps include: immersing in the SAM precursor solution at a speed of 600-1000um / s, staying for 3-6s after being immersed in the solution, and then slowly lifting at the same speed to complete the deposition process, forming a uniform self-assembled monolayer (denoted as Ni-Zr-S) on the surface of the substrate, and obtaining glass / FTO / NiOx / ZrO 2 / SAM substrate.

[0064] Application Example 1

[0065] The glass / FTO / NiOx / ZrO obtained in Example 1 2 / SAM substrate is used to prepare perovskite solar cells, and the specific steps are as follows:

[0066] 1) FAI (0.1462 g), PbI 2 (0.4610 g) and CsBr (0.0319 g) were dissolved in a mixed solvent of DMF and NMP with a volume ratio of 9:1 to prepare FA 0.85 Cs 0.15 PbI 2.85 Br 0.15 Perovskite precursor solution (1.0 M); the perovskite precursor solution was coated on the glass / FTO / NiOx / ZrO obtained in Example 1 at a speed of 18 mm / s and a coating gap of 200 μm. 2 / SAM substrate, and then vacuum treated for 40 seconds, followed by annealing on a hot plate at 130°C for 20 minutes to obtain a perovskite layer;

[0067] 2) PEAI solution (2 mg / mL, solvent: IPA) was scraped onto the top of the perovskite layer at a speed of 15 mm / s with a coating gap of 200 μm and annealed at 70 °C for 10 min;

[0068] 3) Thermal evaporation of C60 (25 nm), BCP (5 nm), and Cu (80 nm) was performed in sequence to complete the preparation of the perovskite solar cell device. The thermal evaporation process was heavy. and The rate (<3×10 -4 ) for evaporation.

[0069] To conduct stability studies, we used The rate of thermal evaporation is Cr 5nm / Bi 20nm / Cu 80nm (<3×10 -4 ). Except for thermal evaporation, the preparation of other layers was carried out in ambient air.

[0070] Example 2

[0071] A self-assembled monolayer, the preparation method of which is substantially the same as that of Example 1, except that: in step 1), a FTO / NiO layer with an area of ​​5×5 cm is prepared. x A layer of SiO is scraped onto the substrate 2 Nanoparticle dispersion (concentration 2wt%, SiO 2 Nanoparticles with a particle size of 5-50nm) are used to prepare FTO / NiO x / SiO 2 / SAM / Perovskite / PEAI / C 60 / BCP / Cu perovskite solar cell devices.

[0072] Comparative Example 1

[0073] A self-assembled monolayer (denoted as Ni-S) is prepared in the same manner as in Example 1, except that the FTO / NiO x The substrate is directly immersed in the Me-4PACz solution in step 2) to perform lift-off coating.

[0074] Comparative Example 2

[0075] A self-assembled monolayer (denoted as Ni-Zr-S) is prepared in the same manner as in Example 1, except that in step 1), a 5×5 cm FTO / NiO x A layer of ZrO is directly coated on the substrate 2 Nanoparticle dispersion (concentration 2wt%, ZrO 2Nanoparticle size is 5-50nm), dried to obtain ZrO 2 Layer modified substrate (FTO / NiO x / ZrO 2 ) This approach cannot produce a uniform and dense self-assembled monolayer.

[0076] Comparative Example 3

[0077] A self-assembled monolayer (denoted as Zr-S), the preparation method of which is substantially the same as that of Example 1, except that the FTO substrate is used instead of the FTO / NiO substrate described in Example 1. x The use of this solution cannot obtain a uniform and dense self-assembled monolayer, and the efficiency and stability of the obtained battery device are lower than those of the battery device obtained under the same conditions in Example 1 (Ni-Zr-S), and the consistency of efficiency is also lower, indicating that the NiO surface also plays an important role in the uniform adsorption of SAM (see Fig.18 and Fig.19 ).

[0078] The FTO / NiO obtained in Example 1 x / ZrO 2 Substrate and FTO / NiO obtained in Comparative Example 1 x The substrate was characterized by scanning electron microscopy, surface potential distribution, X-ray photoelectron spectroscopy, etc. The results are shown in Figure 2 ; It can be seen that compared with FTO / NiO x Substrate ( Figure 2 a), FTO / NiO of the present invention x / ZrO 2 Substrate ( Figure 2 b) A layer of spongy ZrO is continuously distributed on the 2 Nanoparticles; ZrO after high temperature sintering 2 The mesoporous structure provides a large number of evenly distributed voids, which is conducive to the uniform filling of the SAM solution in the subsequent pulling process to form a uniform SAM molecular layer.

[0079] KPFM is used to measure the NiO formed after SAM deposition. x / SAM(Ni-S) and NiO x / ZrO 2 / Surface potential distribution on SAM (Ni-Zr-S) substrate, see Figure 2 c~2d), it can be seen that although SAM can cover most of FTO / NiO x substrate, but there are still some uneven areas; the present invention inserts ZrO 2 After the buffer layer, the coverage of the SAM layer is more uniform, which may be due to the uniform filling of the SAM solution into the ZrO2 The phosphate groups in the mesoporous structure form strong chemical bonds with these surface hydroxyl-rich oxides, which can provide better sites for the growth of high-quality SAM layers. In addition, the surface potential distribution of the selected area was further statistically analyzed, and Ni-Zr-S showed a reduced and more uniform distribution, indicating that the work function of the Ni-Zr-S substrate surface increased and was more inclined to P-type semiconductors, which is beneficial to promote the transport of carriers within the device and inhibit non-radiative recombination at the interface.

[0080] Figure 2 e~2f are X-ray photoelectron spectra of different substrate surfaces. x SAM on substrate, P 2p was observed at 133.9 and 133.1 eV, respectively. 1 / 2 and 2p 3 / 2 The core energy level of FTO / NiO indicates that SAM is successfully adsorbed on the substrate. The existence of Sn 4s peak at 138.9 eV indicates that x Incomplete coverage of the surface. Insertion of ZrO 2 After layer, with FTO / NiO x Compared with the samples, the integrated intensity of the P 2p peak increased slightly, indicating that SAM x / ZrO 2 At the same time, the Sn 4s peak almost disappears, which is consistent with the FTO / NiO x ZrO on substrate 2 The complete coverage of the nanoparticles is consistent, indicating that ZrO 2 The introduction of effectively increases the coverage of SAM, promotes the formation of a more compact monolayer, and reduces the possibility of direct contact between FTO and perovskite.

[0081] The wetting properties of the above-mentioned different substrate surfaces were further characterized, and the contact angle test results are shown in Figure 3 a~b, it can be seen that the contact angle is 63.8° on the Ni-S substrate, while the contact angle is reduced to 35.2° on the Ni-Zr-S substrate, indicating that ZrO 2 The buffer layer can better wet the growth of perovskite.

[0082] The perovskite layer in contact with the charge transport layer was further peeled off to examine the morphology of the buried surface. Obvious morphological defects such as holes ( Figure 3 c), these holes will capture carriers and affect device performance, which may be caused by the large roughness and poor wettability of the Ni-S substrate. x Insert a layer of ZrO between the SAM 2Afterwards, the bottom surface of the perovskite becomes denser and the crystals more uniform ( Figure 3 d). The corresponding cross-sectional view ( Figure 3 e and 3f) were further confirmed (the green mark in the figure is ZrO 2 -NPs). In addition, we also found that the influence of different substrates on the surface morphology and grain size of perovskite films is negligible ( Figure 4 ). The AFM results show that the roughness of the PVK film deposited on the substrate is slightly reduced. Figure 5 As shown in Figure 2, the XRD results show that the diffraction intensity of the (110) peak of the perovskite film on the substrate is enhanced, indicating that the crystallinity is good, as shown in Figure 2. Figure 6 In addition, the UV-Vis results show that ZrO 2 The C-P treatment has little effect on the visible absorption of the perovskite film ( Figure 7 ). The corresponding pictures have been given

[0083] Application example FTO / NiO x / ZrO 2 / SAM / Perovskite / PEAI / C 60 / BCP / Cu structured pi-nPSCs, such as Figure 3 g. The corresponding champion device (0.09cm 2 )'s current density-voltage (JV) curve is as follows Figure 3 h shows that ZrO 2 The device (2wt%) achieved the highest PCE of 25.43%, Voc of 1.174 V, and short-circuit current density (Jsc) of 25.43 mA cm -2 , FF is 85.17%. In contrast, these parameters are 2 The devices with ZrO have poor performance, especially Voc and FF, resulting in a low PCE of 22.79%. 2 With the increasing concentration (3wt%), the efficiency of PSCs decreases, which may be due to the fact that above a certain thickness, the insulating ZrO 2 The nanoparticle layer leads to increased series resistance and poor charge extraction, which reduces the PCE. The corresponding parameters are summarized in Table 1. The distribution statistics of various photovoltaic parameters of different devices are shown in Figure 8 As shown, the data of each statistical graph is extracted from 20 single cells, indicating that the performance of the devices manufactured by this strategy has good reproducibility. The corresponding characterization has been provided. The target champion device achieves a stable PCE of 25.02% at its maximum power point (MPP) and a bias voltage of 0.99V ( Figure 3 i) In addition, different concentrations of ZrO 2 The SEM images are as follows Fig. 9 shown.

[0084] Table 1 Different ZrO 2 Concentration of Cs 0.15 FA 0.85 PbI 2.85 Br 0.15 Photovoltaic parameters of the device

[0085]

[0086] In order to further understand the reasons for the improved device performance, the JV characteristics of devices with different buried interfaces were measured under dark conditions, such as Figure 3 j. Under reverse bias, the current density of the Ni-Zr-S device is lower than that of the Ni-S device. According to the following formula:

[0087]

[0088] Where n is the ideal factor, q is the electron charge, k is the Boltzmann constant, T is the absolute temperature, J ph is the photocurrent density, J 0 is the reverse current density. J of Ni-Zr-S device 0 Lower than Ni-S devices, resulting in V OC This is consistent with the JV curve.

[0089] We also analyzed the V OC , and plotted the logarithmic function of light intensity ( Figure 3 k). Compared with the reference device (n=1.43), the n value of the experimental group device is smaller (n=1.20), which further confirms that the ZrO 2 The defect-assisted non-radiative recombination of the Czochralski device was significantly reduced. 2 After the pull-up treatment, the non-radiative recombination of the device is significantly reduced, and the V OC Increase.

[0090] In order to quantitatively evaluate V OC loss, we measured the reference and ZrO 2 Photoluminescence quantum yield (PLQY) of Czochralski-treated perovskite films (3l). Analysis of the PLQY at the perovskite / transport layer junction revealed a loss of internal quasi-Fermi level splitting (QFLS) in the perovskite bulk and at individual interfaces. An enhancement in the PLQY implies a reduction in non-radiative recombination occurring within the film or at the interface. Higher PLQY values ​​generally lead to an increase in QFLS, and there is a trend toward enhanced device performance with increasing open-circuit voltage. In our work, the change in QFLS after device passivation (ΔQFLS = QFLS passivated -QFLSpristine ) is given by the following equation reported in the literature:

[0091]

[0092] We observed that ZrO 2 The PLQY of the C-treated perovskite film is 0.91%, which is much larger than the 0.22% of the control sample, indicating that the perovskite film has less non-radiative recombination. Therefore, the value of ΔQFLS is calculated to be 36.49 meV; which is equivalent to the V OC The increase is similar.

[0093] The perovskite film was deposited on a 5 × 5 cm substrate (see Fig.10 a). To further explore the uniformity of SAM films prepared by the Czochralski method, five different locations of the perovskite films deposited on different substrates were selected for time-resolved photoluminescence (TRPL) tests. The results showed that no ZrO 2 The control group of nanoparticles showed extremely inhomogeneous electrical effects at five different locations ( Fig.10 d), which may be caused by the uneven SAM during the pulling process. 2 The experimental group of nanoparticles showed remarkable electronic uniformity at five different locations ( Fig.10 e), which indicates that the large-area perovskite film has good uniformity. 2 The mesoporous structure is conducive to the preparation of more uniform SAM films.

[0094] In addition, the perovskite film sample was cut into five pieces on a 5×5 cm Ni-S / PVK (or Ni-Zr-S / PVK) substrate to prepare a perovskite film with an active area of ​​0.09 cm 2 of PSCs. Fig.10 b and c show the JV curves of 5 devices on different substrates. The average PCE of Ni-Zr-S devices is 25.13±0.22%, while the average PCE of Ni-S devices is 22.49±1.17%. Relative to Ni-S samples, all devices of Ni-Zr-S samples show almost the same device performance, and the specific photovoltaic parameters are summarized in Tables 2 and 3. The concentrated distribution of the performance of the 5 devices further verifies the uniformity of the SAM film prepared by this strategy on a large scale.

[0095] Table 2 Photovoltaic parameters of perovskite devices at different locations based on Ni-S substrate

[0096]

[0097] Table 3 Photovoltaic parameters of perovskite devices at different locations based on Ni-Zr-S substrate

[0098]

[0099]

[0100] The recombination and transport properties at the interface of the perovskite buried substrate were further measured using photoluminescence (PL) and other methods. The PL intensity of the perovskite deposited on the Ni-Zr-S substrate is greater than that on the Ni-S substrate ( Fig.11 ), indicating that non-radiative charge recombination in the film is effectively suppressed. The PL intensity gradually increases with the uniform coverage of SAM, indicating that the more compact SAM surface provides more passivation sites for the perovskite layer. The uniform SAM suppressive effect on carrier recombination is also confirmed in the transient photovoltage (TPV) test results ( Fig.12 To explore the carrier transport characteristics at the buried perovskite interface, we also conducted transient photocurrent (TPC) tests. Fig.13 It can be seen that the uniform SAM layer exhibits a lower transient photocurrent, indicating that it is beneficial for the extraction of carriers.

[0101] preparation Fig.14 The device structure shown in a has an aperture area of ​​11.09 cm 2 The mini-module achieved a champion PCE of 22.64% and a Jsc of 4.779 mA cm -2 , Voc is 5.814V, FF is 81.49%, which is comparable to the efficiency of the spin-coated SAM device. The control group device (pin PSCs assembled using Ni-S as described in the comparative example) only achieved a PCE of 19.66%, mainly due to the significant reduction in Voc and FF. Its current-voltage (IV) curve is shown in Fig.14 b, and the corresponding parameters are summarized in Table 4. The filling factor and PCE test results of the obtained mini module size range are shown in Fig.14 c, compared with , it has achieved one of the highest values ​​of fill factor reported so far. The PCE distribution statistics of the reference device and the target device are shown in Fig.14 As shown in d, the data of each statistical graph are extracted from 20 single cells, indicating that the performance of the devices manufactured by this strategy has good reproducibility. The target champion device achieves a stable PCE of 22.38% at its maximum power point (MPP) and a bias voltage of 4.97V.

[0102] Table 4 with or without ZrO 2 Photovoltaic parameters of the champion device (11.09cm2)

[0103]

[0104] We further enlarged the device area to 113.00cm 2 , in order to explore the feasibility of using the Czochralski method to prepare uniform SAM films over a larger area. Fig.14 As can be seen from Figure f, the device efficiency of the SAM layer prepared on a large area Ni-Zr-S substrate by spin coating is significantly lower than that of the device with pulled SAM. This may be due to the unevenness of the large area SAM layer caused by the edge effect of spin coating. For this reason, we also selected 5 different locations on the 14×14 cm substrate for TRPL testing ( Fig.15 and 16 ). It can be seen that on the enlarged substrate, the spin coating method shows uneven electrical effects due to its inevitable edge effect. However, the film prepared by the SAM pulling method is very uniform. Therefore, at 113.00 cm 2 A PCE of 20.11% was achieved on a large-area module, while the device prepared by spin coating only achieved a PCE of 16.35%. The corresponding parameters are shown in Table 5.

[0105] Table 5 with or without ZrO 2 Champion device (113cm 2 ) of the photovoltaic parameters

[0106]

[0107] Finally, we investigated the stability of the control and target devices using Cr / Bi / Cu electrodes. Under 1 sun equivalent illumination, we observed a significant decay of the photoluminescence of the control sample within 5 hours. In contrast, the photoluminescence of the target sample showed almost no significant change during the entire 9-hour tracking time ( Fig.17 ). The corresponding representation is as follows Fig.17 This enhanced PL stability is a strong evidence of the reduced defect density in perovskites. The encapsulated devices showed excellent stability, retaining 92.8% and 94.4% of the initial PCE after 1000 hours of continuous 1 sun equivalent operation at 65°C in air and 500 hours of damp heat test (85°C / 85% RH), respectively. The control group devices only retained 71.4% and 70.1% of the initial PCE, respectively. Fig.14 gh).

[0108] The present invention is not limited to the above-mentioned embodiments. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications are also considered to be within the scope of protection of the present invention. The contents not described in detail in this specification belong to the prior art known to professional and technical personnel in this field.

Claims

1. A method for preparing a self-assembled monolayer, characterized in that: The steps include: 1) Sequentially deposit NiO on a transparent conductive substrate x layer and metal oxide nanoparticle layer, and then sintered at high temperature to form a uniform NiO x layer and a sponge-like metal oxide layer with a mesoporous structure to obtain a substrate modified with a sponge-like metal oxide layer; 2) immersing the obtained substrate modified with the sponge-like metal oxide layer in a SAM precursor solution to perform a lift-off coating; 3) The coating product is baked to form a uniform self-assembled monolayer on the surface of the substrate.

2. The preparation method according to claim 1, characterized in that: The metal oxide nanoparticles are ZrO2 or SiO2, and their particle size is 5-50nm.

3. The preparation method according to claim 1, characterized in that: The thickness of the sponge-like metal oxide layer is 20-150 nm.

4. The preparation method according to claim 1, characterized in that: Step 1) The high temperature sintering step includes: heating to 300-500° C. within 10 minutes, sintering at a constant temperature for 60-120 minutes, and then naturally cooling to room temperature.

5. The preparation method according to claim 1, characterized in that: The NiO x The thickness of the layer is 5-30 nm.

6. The preparation method according to claim 1, characterized in that: The SAM precursor solution is Me-4PACz, MeO-2PACz, MeO-4PACz, 2PACz, Br-2EOTm, MPA-Ph-CA, Br-2EPT, MTPA-BA or CbzNaph solution, and its concentration is 0.4-1.0 mg / ml.

7. The preparation method according to claim 1, characterized in that: In the lifting coating process, the substrate modified with the obtained sponge-like metal oxide layer is immersed in the SAM precursor solution at a speed of 600-1000um / s, and after being immersed in the solution, it stays for 3-6s and then is lifted at the same speed to complete the coating process.

8. The preparation method according to claim 1, characterized in that: The NiO x The area of ​​the modified transparent conductive substrate is 0.09 cm 2 above.

9. The self-assembled monolayer prepared by the preparation method according to any one of claims 1 to 8, characterized in that: Its thickness is 2-5 nm and the contact angle is reduced to 35.2°.

10. A perovskite solar cell based on the self-assembled monolayer according to claim 9, characterized in that: The perovskite layer is placed on the surface of the self-assembled monolayer.

Citation Information

Cited By

  • Preparation method of self-assembled bilayer and perovskite solar cell

    CN121057478A